Visual motion and rapid auditory processing are solid endophenotypes of developmental dyslexia. (14th September 2017) - Mascheretti, S.; Gori, S.; Trezzi, V.; Ruffino, M.; Facoetti, A.; Marino, C.
Abstract : Although a genetic component is known to have an important role in the etiology of developmental dyslexia (DD), we are far from understanding the molecular etiopathogenetic pathways. Reduced measures of neurobiological functioning related to reading (dis)ability, i.e. endophenotypes (EPs), are promising targets for gene finding and the elucidation of the underlying mechanisms. In a sample of 100 nuclear families with DD (229 offspring) and 83 unrelated typical readers, we tested whether a set of well‐established, cognitive phenotypes related to DD [i.e. rapid auditory processing (RAP), rapid automatized naming (RAN), multisensory nonspatial attention and visual motion processing] fulfilled the criteria of the EP construct. Visual motion and RAP satisfied all testable criteria (i.e. they are heritable, associate with the disorder, co‐segregate with the disorder within a family and represent reproducible measures) and are therefore solid EPs of DD. Multisensory nonspatial attention satisfied three of four criteria (i.e. it associates with the disorder, co‐segregates with the disorder within a family and represents a reproducible measure) and is therefore a potential EP for DD. Rapid automatized naming is heritable but does not meet other criteria of the EP construct. We provide the first evidence of a methodologically and statistically sound approach for identifying EPs for DD to be exploited as a solid alternative basis to clinical phenotypes in neuroscience. Abstract : Criterion 4 results. The 50% threshold mean for the rotating‐tilted‐lines illusion (RTLI) task (a). The slope mean of the fitted function for the RTLI (b). Mean accuracy among the five inter‐stimulus intervals of the rapid auditory processing task (c). Warning effect (d). Age and socio‐economic status are included as covariates. Aff, subjects with DD; UnAffSibs, unaffected siblings; TR, typical readers. *Two‐tailed significant P ‐value < 0.05; ** two‐tailed significant P ‐value < 0.001.